ANALISIS PERAN HUMAN RESOURCE BUSINESS PARTNER DALAM PENGELOLAAN SDM DI PT. TELKOM AKSES SINGARAJA - Ni Made Ita Kusuma Wardani; I Gusti Ketut Adi Winata (CV. Lafadz Jaya, 2026)
This study aims to describe the HRM functions carried out, the role of the HR Business Partner (HRBP), and the factors supporting and hindering the implementation of the HRBP role at PT. Telkom Akses Singaraja. This study employs a qualitative research method, specifically a descriptive qualitative approach; data collection was therefore conducted through interviews, observation, documentation and triangulation. Interviews involved key informants and supporting informants, ensuring that the information provided was triangulated prior to analysis. Data analysis in this study utilised the Miles & Huberman (1984) analytical model and drew upon the concept of the four roles of the HRBP, namely Strategic Partner, Administrative Expert, Employee Champion and Change Agent. The research findings indicate that the HRM functions carried out at PT. Telkom Akses Singaraja include organisation, control, recruitment, development, compensation, retention and discipline. The reflection of the HRBP roles is derived from the implementation of HRM functions in the Singaraja area; the Strategic Partner role is reflected through the coordination between head office and the regional office. The role of Administrative Expert is reflected through administrative services provided by the HR department, supported by digital systems; consequently, this role is the most prominent, given the HR department’s focus on administrative tasks in the region. The role of Employee Champion is reflected through the provision of counselling to resolve workplace conflicts, as well as structured training to develop employees’ competencies. The Change Agent role is reflected in the communication of information regarding changes occurring within the company through awareness-raising sessions, sharing sessions or announcements at weekly roll calls, extending to internal groups. Factors supporting the implementation of the HRBP in the Singaraja area include employee responsiveness, structured training programmes, counselling, and coordination between the regional office and head office. Meanwhile, the inhibiting factors consist of the vast geographical extent of the operational area, limited HRD personnel, and constraints in the decision-making process. Thus, the implementation of the HRBP at PT. Telkom Akses Singaraja is reflected in human resource management, but still requires strengthening in its strategic role.